FOETAL HAEMOGLOBIN AND DISEASE SEVERITY IN NIGERIAN CHILDREN WITH SICKLE CELL ANAEMIA. - Oluwagbemiga Adeodu; Morenike Akinlosotu; Samuel Adegoke; Saheed Oseni (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Foetal haemoglobin (HbF) is a major modifying factor influencing sickle cell disease (SCD) severity. Despite this, HbF estimation is not routinely done in Nigeria. Relationship between HbF and SCD severity among affected children is also poorly studied.